Ecological characteristics of mangroves and coral reefs at Central Weda Sub-District, North Maluku. Issue 1 (October 2021) - Lessy, M R; Bemba, J; Wahiddin, N; Supyan,; Taeran, I; Galitan, Z
Abstract: Increase of human activities on coastal area in Central Weda Sub-District has caused degradation of coastal ecosystems. Even though coastal ecosystems have an essential role in marine ecology, such as coral reefs and mangrove forests, they are sometimes undermined by economic or commercial interests. This study aimed to determine density and cover percentage of mangrove forests and coral reefs in Central Weda Sub-district, North Maluku. Data collection on coral reef ecosystem components was carried out by applying georeferenced photo-transect and line transect quadrat techniques. While for mangroves, data collection included species diversity and tree/canopy cover percentage. Study result showed that based on lifeform percentage of coral reefs, most of the study areas were in a good category with 23.95% coverage, moderate condition 39, 5%, and poor condition 36.6%. The coral reefs in good and moderate conditions were found at location having relatively low human activities. Whereas percentage of mangrove cover from all stations ranged from 78, 39 to 78, 76% with Important Value Index ranging from 106, 79% to 158, 32%.